Cases of Brainstem Infarcts after Cessation of Heparin Treatment: Is It a Rebound Effect? - Demir, Caner Feyzi; Surgun, Fidan; Ozdemir, Hasan; Kapan, Oktay (Aves, 2011)
The presented cases represent patients with acute coronary syndrome treated with heparin infusion who developed brainstem infarction after discontinuation of heparin treatment. The patients did not present genetic coagulopathy. Others risk factors were analyzed, and the discontinuation of heparin infusion was also considered to have a predominant role in the development of infarction.
Keywords: Cerebrovascular diseases; Heparin; Rebound effect